Automatic machine learning algorithms for fraud detection in digital payment systems - Kolodiziev, O.; Mints, A. Yu.; Sidelov, P.; Pleskun, I.; Lozynska, O.; Мінц, О. Ю. (PC TECHNOLOGY CENTER, 2020)
Data on global financial statistics demonstrate that total losses from fraudulent transactions around the world are constantly growing. The issue of pay-ment fraud will be exacerbated by the digitalization of economic relations, in particular the introduction by banks of the concept of "Bank-as-a-Service", which will increase the burden on payment services. The aim of this study is to synthesize effective models for detecting fraud in digital payment sys-tems using automated machine learning and Big Data analysis algorithms.Approaches to expanding the information base to detect fraudulent transactions have been proposed and systematized. The choice of performance metrics for building and comparing models has been substan-tiated.The use of automatic machine learning algorithms has been proposed to resolve the issue, which makes it possible in a short time to go through a large num-ber of variants of models, their ensembles, and input data sets. As a result, our experiments allowed us to obtain the quality of classification based on the AUC metric at the level of 0.977‒0.982. This exceeds the effectiveness of the classifiers developed by tradition-al methods, even as the time spent on the synthesis of the models is much less and measured in hours. The models' ensemble has made it possible to detect up to 85.7 % of fraudulent transactions in the sample. The accuracy of fraud detection is also high (79‒85 %).The results of our study confirm the effectiveness of using automatic machine learning algorithms to synthesize fraud detection models in digital payment systems. In this case, efficiency is manifested not only by the resulting classifiers' quality but also by the reduction in the cost of their development, as well as by the high potential of interpretability. Implementing the study results could enable financial institutions to reduce the financial and temporal costs of developing and updating active systems against payment fraud, as well as improve the effectiveness of monitoring financial transactions.
Keywords: digital payments; machine learning; automated synthesis; fraud detection; data science